2020
DOI: 10.1371/journal.pone.0234124
|View full text |Cite
|
Sign up to set email alerts
|

Health anxiety and illness-related fears across diverse chronic illnesses: A systematic review on conceptualization, measurement, prevalence, course, and correlates

Abstract: Background Patients with chronic diseases commonly report fears of illness or symptoms recurring or worsening. These fears have been addressed from an illness-specific perspective (e.g., fear of cancer recurrence), a generic illness perspective (e.g., fear of progression), and a psychiatric perspective (DSM-5 illness anxiety disorder and somatic symptom disorder). The broader concept of health anxiety (HA) can also be applied to patients with a chronic disease. This review was conducted to investigate the conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
75
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 278 publications
(370 reference statements)
5
75
0
3
Order By: Relevance
“…Therefore, given these findings, it can be suggested that HA, unlike other constructs, may show characteristics of both transient distress and psychopathology depending on the level of effect on self-concept. In contrast, a recent review on the correlates of FCR found that this concept was on the whole rather stable, or perhaps could initially decrease then stabilize (Lebel et al, 2020). Worry was uniquely related to the theoretical attribute of self-focused attention.…”
Section: Overview Of Unique Attributesmentioning
confidence: 79%
See 2 more Smart Citations
“…Therefore, given these findings, it can be suggested that HA, unlike other constructs, may show characteristics of both transient distress and psychopathology depending on the level of effect on self-concept. In contrast, a recent review on the correlates of FCR found that this concept was on the whole rather stable, or perhaps could initially decrease then stabilize (Lebel et al, 2020). Worry was uniquely related to the theoretical attribute of self-focused attention.…”
Section: Overview Of Unique Attributesmentioning
confidence: 79%
“…Finally, one trigger, unmet information needs, was identified in both FCR and uncertainty and is consistent with the literature. Insufficient and inaccurate information about cancer prognosis and recurrence risks are known to contribute to fear and uncertainty among breast cancer survivors (Lebel et al, 2014(Lebel et al, , 2018(Lebel et al, , 2020.…”
Section: Overlapping Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fear of progression (FoP) is a common experience for people with chronic illness. 53 , 54 The current FCR definition 1 refers not only to fear of recurrence experienced by cancer survivors with no evidence of disease but also to FoP experienced by patients with active cancer. One of the arguments for this broad definition has been that the distinction between “patients” and “survivors” is far from clear-cut, not only in the clinical oncology setting, but also in how people diagnosed with cancer view themselves.…”
Section: Resultsmentioning
confidence: 99%
“…However, this response is exacerbated in vulnerable groups, in whom perceived life threat is known to be associated with negative mental health outcomes during epidemics (23). Persons with chronic disease often live with health‐related anxiety in general (24), and the threat of COVID‐19 infection has the potential to exacerbate this anxiety. According to the CDC, persons taking immunosuppressant medication (such as many patients with autoimmune diseases) might be at increased risk of severe illness from COVID‐19 infection (19).…”
Section: Methodsmentioning
confidence: 99%